Probing and modulating brain circuits by deep brain stimulation - Wu, D (2015)
Backgrounds. The periaqueductal grey(PAG) plays an important role in the descending pain modulation systems, which has been known to inhibit incoming nociceptive signals at the level of the spinal dorsal horn. But pain mechanism involves the brain and the spinal cord to maintain homeostasis, so theoretically pain modulation mechanism should involve both direction: ascending and descending pathways to the brain and spinal cord dorsal horn. However, literature addressing this question is limited. The sensory thalamus is the most important brain area receiving sensory signals. Moreover, with the fact that evidence indicates the PAG and the thalamus have functional connections, therefore we wanted to test if there is a functional connection between the PAG and the sensory thalamus related to pain modulation. Aims. To investigate the functional connectivity between the periaqueductal grey and the sensory nuclei of the thalamus in pain modulation Methods. Three experiments have been conducted. The first experiment is to investigate the effect of PAG DBS on the sensory thalamus, and vice versa, in chronic neuropathic pain patients. The second experiment is to estimate the change of spectral coherence between the sensory thalamus and the PAG during various pain states, when chronic neuropathic pain patients were being peripheral stimulated by ice to evoke pain. The third experiment is to test whether the functional connectivity between the two areas would be affected by general anaesthetics propofol. Results. PAG DBS inhibited the sensory thalamus with decreasing thalamic delta, theta, alpha and beta power, and sensory thalamus DBS excited the PAG with increasing PAG delta and theta power. The PAG and the sensory thalamus interact reciprocally at short latency, which may be related to pain modulation. The sensory thalamus and the periaqueductal grey also have high gamma coherence which would be inhibited by pain. This high-gamma coherence was increased during propofol induction period which is compatible with the hypothesis that propofol induces loss of consciousness via its GABAergic activity. Conclusions. This thesis suggests that the sensory thalamus and the periaqueductal grey have a reciprocal connection. Functionally this connectivity might be related to pain modulation. Also this functional connectivity might represent the fact that the transmission and processing of pain signals is always monitored and modified by central pain modulation systems so that organisms can respond properly to the incoming signals.